Evalvacija zaznavno-motoričnih sposobnosti za ugotavljanje učinkovitega vedenja v varnostno zahtevnih situacijah - Čeh, Matej (Psihološka obzorja (Ljubljana), 2021)
A person's ability to behave effectively in demanding work situations at work is evaluated as part of a psychological assessment of work ability. Workplaces, where the visual and motor skill loads are assessed as above average, adequate psychomotor skills of the worker are required. In this paper we present the results of a research performed on a sample of 198 candidates and employees in workplaces from the fields of first response, health, safety, and security. We evaluated the psychomotor abilities of the individuals included in the research by using tests of visual orientation, visual motor coordination, and differentiated motor responsiveness. The results were compared according to the way stimuli were presented (active or adaptive), the type of motor activity (discrete or continuous), and the responses/stimuli ratio. Analysis shows that individuals with faster responses are more effective with discrete motor tasks. To perform continuous motor tasks under time pressure, the individual must have adequate balance of psychomotor functions, which is determined with the speed and accuracy ratio response. The analysis shows that there are statistically significant differences in the ability of participants to keep accurate responses under time pressure. These differences show the psychomotor response style that either favours speed or accuracy. We conclude that the speed and accuracy of motor reactions is not sufficient to provide a comprehensive assessment of the psychomotor capability. When evaluating the ability to perform adequately in work with higher risk conditions it is necessary to consider the ratio between speed and accuracy, as well as the capability of maintaining adequate motor reactions under time pressure.
Keywords: delovna učinkovitost; delovne veščine; employee efficiency; employee skills; Preizkus enostavne orientacije v polju (CRD2) testnega sistema CRD; Preizkus razpršene pozornosti in motoričnega odzivanja (DT-S1) testnega sistema VTS; Preizkušnji enostavne (CRD4a) in diferencialne (CRD4b) vidno motorične koordinacije testnega sistema CRD; psihološko ocenjevanje; reaction time; reakcijski čas; vidno-motorična integracija; visual motor integration